Design and Analysis of Home Automation Systems Based on MAC Address - Muhammad Aden Fahadi; Yuwaldi Away; Ira Devi Sara (LPPM Politeknik Aceh Selatan, 2020)
Home Automation is one of the advances in technology and communication by automating the control of electrical devices at home. With this method, home electronic devices can be controlled using a remote control system without having to touch the home appliances themselves. Along with the development of the operating system on mobile devices gives birth to innovation and creativity that is in line with the needs of its users, from mere communication tools to information centers. One of the innovations in the field of daily life of its users is Home Automation which allows control of electrical devices so that it can save electricity consumption at home that can be done remotely both in the same location or in other rooms with sensors and user interface design from Android to simplify monitoring. The Home Automation application communicates via MAC addresses on Android registered in Wemos D1, which Android can be used to control automatically, in this study using the Wemos D1 module as a brain or control center that will receive data from Android for later processing to the lamp output , motion sensor (PIR), DHT22 sensor, fan, and door lock by using a solenoid that can be controlled automatically from any sensors connected to the Wemos D1 microcontroller.